Matrix transformations of starshaped sequences - Chikkanna R. Selvaraj; Suguna Selvaraj (International Journal of Mathematics and Mathematical Sciences)
We deal with matrix transformations preserving the starshape of sequences. The main result gives the necessary and sufficient conditions for a lower triangular matrix A to preserve the starshape of sequences. Also, we discuss the nature of the mappings of starshaped sequences by some classical matrices.